Why do Gen Z choose teaching as careers? exploring extrinsic motivations of Gen Z to become teacher in Indonesia - Suyatno, Suyatno; Patimah, Lilis; Wantini, Wantini; Maryani, Ika; Hasanah, Enung; Arqam, Mhd. Lailan; Fadlillah, M. (Intelektual Pustaka Media Utama, 2026)
The decision to become teacher is greatly influenced by certain motivations such as altruistic, intrinsic, and extrinsic. Examining these motivations influencing individuals’ decisions to become teachers is essential for sustainable professional development. This is because no previous publication has focused on Generation Z’s (Gen Z) extrinsic motivations to pursue teaching profession. Therefore, this study aimed to explore motivations of Gen Z to become teachers in elementary schools. A qualitative analysis was adopted with a focus group discussion method including 58 pre-service teachers learning at the primary school teacher education program. Furthermore, the participants in the analysis were aged 18-22 years and also fell into the Gen Z category. Data obtained from the participants was further analyzed using thematic analysis. The results showed that extrinsic motivations underlying the desire of Gen Z to become teachers originated from the high social respect teaching receives from society, the promise of prosperity, and adequate employment opportunities. Extrinsic motivations also originated from childhood experiences inspired by religious teachings and the parents. The study further emphasized the importance of understanding the participants’ motivations for entering teaching profession to improve recruitment systems, providing motivation, set hours and workloads, as well as welfare systems for Gen Z teachers.